Evaluation of Wastewater Pollution and Treatment Efficiencies in China During Urbanization Based on Dynamic Exogenous Variable Data Envelopment Analysis - Sun, Yanan; Ren, Fangrong; Liu, Jiawei; Shi, Naixin; Wang, Haofei; You, Xiaotong (Frontiers in Environmental Science, 2021)
Under the comprehensive reform of its household registration system, China has experienced the largest and fastest urbanization process in the world since its establishment 70 years ago, but with the deepening of urbanization, cities are facing greater environmental challenges. As the total amount of urban wastewater discharge increases, the condition of water pollution nationwide has become more severe. Thus, through the use of dynamic exogenous variable data envelopment analysis (DEA) this research selects the employment population and input cost of wastewater treatment in 31 provinces of China from 2013 to 2017 as input indicators, gross domestic product (GDP), wastewater production, and chemical oxygen demand (COD) in wastewater as output indicators, fixed assets as a carry-over variable, and urbanization level as an important influencing factor to evaluate and compare wastewater treatment efficiency in the northeast, central, western, and eastern regions with and without the influence of the level of urbanization. Findings show that the total efficiency score under the influence of the level of urbanization is generally higher than that without such an influence. The level of urbanization has a significantly positive effect on wastewater output efficiency in various regions, whereas wastewater output efficiency presents a downward trend from 2013 to 2017. The overall level of chemical oxygen demand efficiency is weak. When affected by the level of urbanization, the scores of COD efficiency in the eastern, northeast, and central regions have increased significantly. Finally, there is a large inter-provincial gap in the level of urbanization in the western region, while the level of urbanization has no significant impact on COD efficiency.